2023
DOI: 10.1126/sciadv.adg4846
|View full text |Cite
|
Sign up to set email alerts
|

Essential autoproteolysis of bacterial anti-σ factor RsgI for transmembrane signal transduction

Chao Chen,
Sheng Dong,
Zhaoli Yu
et al.

Abstract: Autoproteolysis has been discovered to play key roles in various biological processes, but functional autoproteolysis has been rarely reported for transmembrane signaling in prokaryotes. In this study, an autoproteolytic effect was discovered in the conserved periplasmic domain of anti-σ factor RsgIs from Clostridium thermocellum , which was found to transmit extracellular polysaccharide-sensing signals into cells for regulation of the cellulosome system, a polysaccharide-degrading mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…While this study was under review, Chen et al reported NMR and crystal structures of the SEAL domains from H. thermocellum RsgI1, RsgI2, and RsgI6 and the finding that these domains undergo autoproteolysis, as we have described here ( 30 ). The structures of the cleaved H. thermocellum SEAL domains have a similar fold to B. subtilis RsgI GGG and contain analogous extensions of the β-strands proximal to the cleavage site.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…While this study was under review, Chen et al reported NMR and crystal structures of the SEAL domains from H. thermocellum RsgI1, RsgI2, and RsgI6 and the finding that these domains undergo autoproteolysis, as we have described here ( 30 ). The structures of the cleaved H. thermocellum SEAL domains have a similar fold to B. subtilis RsgI GGG and contain analogous extensions of the β-strands proximal to the cleavage site.…”
Section: Discussionsupporting
confidence: 57%
“…3 A ). A recent report provides strong support for this model and implicates the H. thermocellum RasP homolog as the site-2 protease ( 30 ).…”
Section: Resultsmentioning
confidence: 88%
“…NMR structure calculation procedures were similar to those previously described (Chen et al, 2023; Wei et al, 2019). Initial dDoc_0689 structures were calculated using the CYANA (Herrmann et al, 2002) software with the NOE peak lists from the 3D 15 N‐edited and 13 C‐edited NOESY HSQC spectra and dihedral angle restraints derived from the chemical shifts using the program TALOS‐N (Shen & Bax, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The modules within the cellulosome are connected by flexible linkers, allowing the cellulosome to undergo conformational changes according to the substrate, thus degrading the substrate better [162]. Additionally, bacteria express genes of cellulosomal components dynamically based on the type of substrate and adapt to the different substrate compositions [162][163][164][165][166]. Compared to free cellulases, cellulosomes not only exhibit a stronger tolerance to chemical inhibitors such as formate, lactate, and furfural present in the hydrolysate but also show a higher ethanol tolerance and thermostability [157].…”
Section: Saccharification Processmentioning
confidence: 99%